SEJARAH PEMIKIRAN ISLAM DI DUNIA TERHADAP PENDIDIKAN: Indonesia - AHMAD RIFFAI; Dwi Alvin Rahmawati; Fiddini Iffah Ayuda; Ahmad Rifa'i (Mukaddimah: Jurnal Studi Islam, 2023)
This research explains about how the history of Islamic thought influences the progress of education, because it is no longer a taboo for us that Islam contributes many thoughts to the progress of education. for us that Islam contributed many thoughts to the progress of education and civilization. and civilization. Therefore, to find out what thoughts were given by Islam, we investigate the evolution of Islamic educational thought from time to time. Islam we investigate the evolution of Islamic educational thought over time, and the relationship between the history of Islamic thought and the history of Islamic education. period, and the relationship between the history of Islamic thought and the progress of Islamic education. This research is included in the cluster with a literature review approach and historical analysis whose data is taken from previous studies. taken from previous studies. The results of the research reveal the peaks of thought in Islamic history that influenced Islamic education. that influenced Islamic education. In addition, we analyze how Islamic education evolves in the face of contemporary challenges, illustrate the interrelationship between global and local thought in the context of Islamic education. This research contributes to our understanding of the revolution in education and Islam's great role in being the driving rotor for the changes in civilization and education that developed in its time. for changes in civilization and education that developed in its time. So for the the development of educational thought, this is an important capital for Islamic education to further develop its potential in the era of the industrial revolution 4.0 to 5.0 now. its potential in the era of the industrial revolution 4.0 to 5.0 today.   Keywords: Historis; Thingking; Education